User-generated content or user-generated data? The (un)voluntary dynamics of online content generation - Santos, Marcelo; Román Aponte, Luján (InMediaciones de la Comunicación, 2025)
The increasing datafication and the involuntary generation of data –simply by interacting, with varying degrees of awareness, with a wide range of digital social platforms– calls for a reassessment of the concept of User-Generated Content (UGC). In this regard, the notion of User-Generated Data (UGD) is proposed, based on an idea that is frequently invoked but rarely discussed in academic literature. The discussion focuses on how users’ digital traces are captured and processed by third parties. A critical analysis is then offered, distinguishing and delineating the concepts of UGD and the definition of UGC, arguing that they represent two distinct research strands from which online content generation can be approached.